Draft Genome Sequence of Chromobacterium haemolyticum Causing Human Bacteremia Infection in Japan - Miki, Tsuyoshi (Genome Announc, 2014)
Chromobacterium haemolyticum is a Gram-negative bacterium displaying remarkable hemolysis against human and sheep erythrocytes. In addition, C. haemolyticum infects humans, in which the infection mechanism remains unknown. We report here the draft genome sequence of C. haemolyticum strain T124, isolated from a young patient with sepsis in Japan.